2005
DOI: 10.1089/ten.2005.11.458
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Model Using Three-Dimensional Cultivation of Preadipocytes Seeded onto Fibrous Polymer Scaffolds

Abstract: A better understanding of the mechanism of adipose tissue differentiation is of paramount importance in the development of therapeutic strategies for the treatment and prevention of obesity and type 2 diabetes mellitus. Optimal results using tissue culture models can be expected only when the in vitro adipocyte resembles adipose tissue in vivo as closely as possible. In this study, we used tissue-engineering principles to develop a three-dimensional (3-D) culture system to mimic the geometry of adipose tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 47 publications
2
52
0
1
Order By: Relevance
“…The open, porous structure acts as a preserver of space for efficient cellular adhesion and seeding and facilitates vessel ingrowth with subsequent mass transport of oxygen and nutrients. The three-dimensional geometry of the native ECM constrains cells during regeneration and provides space for tissue development [25] and in vitro studies have shown that the scaffold geometry promotes preadipocyte differentiation [31]. The architecture of adipose tissue has been reconstructed using adipose-derived stromal cells seeded onto different scaffold materials [6][7][8]13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The open, porous structure acts as a preserver of space for efficient cellular adhesion and seeding and facilitates vessel ingrowth with subsequent mass transport of oxygen and nutrients. The three-dimensional geometry of the native ECM constrains cells during regeneration and provides space for tissue development [25] and in vitro studies have shown that the scaffold geometry promotes preadipocyte differentiation [31]. The architecture of adipose tissue has been reconstructed using adipose-derived stromal cells seeded onto different scaffold materials [6][7][8]13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cell-based approaches utilizing adipogenic progenitor cells in combination with biomaterial carriers for fat tissue engineering have been developed and were reported to promote both short-term in vivo adipogenesis and to repair defect sites [8][9][10][11][12][13][14]. For these cellbased applications, human mesenchymal stem cells derived from bone marrow (hMSCs) or human adipose tissue (hASCs) have both been suggested as potential cell sources for adipose repair therapies [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For these cellbased applications, human mesenchymal stem cells derived from bone marrow (hMSCs) or human adipose tissue (hASCs) have both been suggested as potential cell sources for adipose repair therapies [13][14][15][16]. hMSCs and hASCs are readily isolatable from bone marrow aspirates or adipose stromal vascular fractions, respectively, and can differentiate into a variety of mesenchymal lineages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of adipogenic progenitor cells derived from hTGSCs may also emerge as a promising approach for cell-based adipose tissue engineering with various clinical implications: fatty defects are usually seen after traumas, deep burns, tumor resections such as mastectomies, and are important in cosmetic facial problems involving the cheek, chin, and jaw. [35][36][37] In contrast, P85 had no significant impact on the fatty acid profile of hTGSCs; however, it displayed considerable cytotoxic effect during differentiation even at low concentrations (0.01%, 0.05%). P85 is generally used for the inhibition of the Pgp drug efflux system, which is crucial for improved delivery of Pgp-dependent molecules through the blood-brain barrier, intestinal tight-junctions, and MDR-tumors.…”
mentioning
confidence: 90%